Effect of denosumab treatment on bone mineral density and bone turnover markers in osteoporotic patients: real-life experience 2-year follow-up - DİNÇER YAZAN, CEYDA; BUĞDAYCI, ONUR; ILGIN, CAN; YAVUZ, DİLEK (My University, 2022)
Summary Denosumab leads to improvements in BMD levels and is a well-tolerated agent according to results of randomized controlled studies but results in real-life setting are important to evaluate drug adherence and real-life efciency. In this study, we present the results of 305 patients that were treated with denosumab in our clinic. Introduction The long-term efcacy of anti-osteoclastic drugs in treatment of osteoporosis is well known. Denosumab, a novel human monoclonal antibody, is an anti-osteoclastic agent that has been shown to lead to reductions in vertebral, nonvertebral, and hip fracture risk in randomized and observational studies. Real-life data of this agent is increasing. In this study, we presented our real-life data about the 2-year follow-up of patients under denosumab treatment. Methods Osteoporotic patients who were treated with at least one denosumab injection between 2014 and 2020 years were included. Clinical and demographic data, bone turnover markers, and radiological reports (bone mineral densitometry (BMD), vertebral x-ray) were obtained from patient fles retrospectively. Results A total of 305 patients (f/m: 275/30, 68.1±11.05 years) were included. The median injection number was 4 (1–10). Two hundred seventy-three patients (89.8%) were persistent on treatment at the 12th month; 175 patients (57.3%) were persistent at 24th month. Sixty-eight patients (22%) were not using denosumab anymore, 55 of the patients were not continuing by doctor desicion and 13 were not continuing due to patient-related causes. Median BMD levels signifcantly increased from 0.809 (0.2–1.601, IQR: 0.136) to 0.861 (0.517–1.607, IQR: 0.14) in L1–L4 and from 0.702 (0.349–0.997, IQR: 0.125) to 0.745 (0.508–1.008, IQR: 0.137) in femur area at the 24th month of treatment. An improvement of 8.04% in L1–L4 BMD and 4.5% in femur neck BMD levels at the 24th month of treatment was observed. There was a signifcant decrease in bone turnover markers at the 24th month of treatment. Conclusion In our group of patients under denosumab treatment, 53% of persistence was found at 24 months and associated with improvement in BMD levels without any signifcant side efects except one case with urticarial reaction. Denosumab leads to improvements in BMD levels and is a well-tolerated agent in a real-life setting comparable to results of randomized controlled studies in patients with diferent comorbidities.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Cerrahi Tıp Bilimleri; Ortopedi ve Travmatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Endocrinology and Metabolic Diseases; Surgery Medicine Sciences; Orthopedics and Traumatology; Health Sciences; ENDOKRİNOLOJİ VE METABOLİZMA; Klinik Tıp; Klinik Tıp (MED); ORTOPEDİ; ENDOCRINOLOGY & METABOLISM; CLINICAL MEDICINE; Clinical Medicine (MED); ORTHOPEDICS; Ayak Bakımı; Endokrin ve Otonom Sistemler; Ortopedi ve Spor Hekimliği; Endokrinoloji, Diyabet ve Metabolizma; Endokrinoloji; Yaşam Bilimleri; Podiatry; Endocrine and Autonomic Systems; Orthopedics and Sports Medicine; Endocrinology, Diabetes and Metabolism; Endocrinology; Life Sciences; Denosumab; Bone mineral density; Real-life experience